It takes a village to support the National Park Service - Espinosa, Tiffany, author; Vaske, Jerry V., advisor; Donnelly, Maureen P., committee member; Bright, Alan, committee member; Morgan, George, committee member (Colorado State University. Libraries, 2016)
As the United States becomes more diverse, the National Park Service will need to continue to adapt if it is going to continue to garner public, political, and financial support in the future. In these three chapters, the role of citizens, funders, politicians and visitors is investigated. The first two chapters of this study explore the historic role of citizens and legislators in creating and developing the National Park System. The third chapter takes park visitor data, joined with market research data, to explore different theories on barriers for diverse audiences, in-group heterogeneity of park visitors, and opportunities to use this research to engage new park visitors and boosters from diverse backgrounds. The first chapter provides a historical perspective on the origins of the National Park Service. This chapter considers the early advocates and park champions from all walks of life who helped shaped the system in its earliest years. In particular it focuses on those outside the government bureaucracy who helped provide the infrastructure and resources, and who got the country energized around the concept of government investment in conservation and heritage work. The second chapter explores political aspects of designating new sites into the National Park System. Federally designated protected lands represent a variety of political, economic, recreational and ideological costs and benefits. The chapter reviews some of the main arguments for and against creating new National Park sites, the legislative steps that proposed parks go through in the process to become an official national park unit, and tests the electoral competition theory, an adaptation of economic rational choice theory applied to political behavior. The electoral competition theory hypothesizes that as the congressional majority margin decreases (gets more competitive), politicians will act in a more strategic & less partisan manner. This study examined the creation of new National Park units from 1934-2010 in the US, and found evidence in support of partisanship, electoral competition, and that presidential election years heightened the competitive behaviors of legislators. This suggests that the evolution of the parks system has been influenced by political interests and political gamesmanship. The third chapter explored in-group racial and ethnic heterogeneity among National Park visitors. Park visitation rates for minority visitors are low compared to white visitors. Teasing out the in-group heterogeneity of visitors provides park administrators with better information on which specific audience segments they are currently drawing to the parks. In this study three theories were tested to evaluate and compare the role of (a) cultural differences, (b) affluence and proximity, and (c) an integrated model that includes race, resources, geography, and lifestyles factors in specifying statistically relevant differences between and within groups. For the study, park visitor information was joined with psychographic and geo-demographic data. The results show that there is significant heterogeneity within racial or ethnic groups and the model with the strongest effect size is the integrated model that considers visitors in a broadest context, though each model provided insights about visitor heterogeneity. Also included was a sample of ways park administrators could apply the information from the study to develop targeted outreach and programming.